Plants mitigate detrimental nitrogen deposition effects on soil biodiversity. (December 2018) - Shao, Yuanhu; Liu, Tao; Eisenhauer, Nico; Zhang, Weixin; Wang, Xiaoli; Xiong, Yanmei; Liang, Chenfei; Fu, Shenglei
Abstract: Anthropogenic nitrogen (N) deposition is an important component of global change and threatens terrestrial biodiversity. Most previous studies of the consequences of N deposition have focused on plant community responses and found that N deposition decreases plant diversity. However, the effects of N deposition on soil biodiversity and belowground biotic interactions remain poorly understood. We explored the changes in main soil food web components (microbes, nematodes, springtails, and mites) in response to elevated N deposition (60 kg N ha −1 yr −1, starting from 2012 to 2014), and whether these changes are altered by the presence of plants (planting of shrubs in 2008) in a two-factorial field mesocosm experiment with 16 equally-sized plots (1 × 2 m). Our results showed that elevated N deposition negatively affected soil bacteria, while fungi showed rather neutral responses. Specifically, N deposition decreased bacteria Shannon's diversity index H′, richness, observed species abundance, bacterial activity, and resulted in a non-significant decrease of the relative abundance of rare bacterial taxa. By contrast, for fungi, only a non-significant decrease of richness was observed with N deposition. Importantly, those N deposition effects mostly occurred in the absence of planted shrubs. Moreover, shrub presence and N deposition also interactively affected the diversity of soil invertebrates, i.e., N deposition had little effect on them in the absence of planted shrubs, but resulted in an increase or a non-significant increase of soil invertebrate diversity in the presence of planted shrubs. Furthermore, N deposition did not affect the biomass/density of any soil food web component and biomass/density ratios related to soil food web structure regardless of absence or presence of planted shrubs; these indices were only affected by the presence of shrubs. Overall, these dissimilar responses of the diversity of soil microorganisms and animals to elevated N deposition indicate that plants are important mediators of N deposition effects on soil biodiversity. Thus, the present results may imply that an intact plant cover may mitigate detrimental N deposition effects on soil biodiversity. Highlights: N deposition decreased soil bacterial diversity and activity. Effects of N deposition on soil microbes primarily occurred in the absence of plants. N deposition had little effect on soil faunal taxa in the absence of plants. N deposition tended to increase soil faunal diversity in the presence of plants. Plants are important mediators of N deposition effects on soil biodiversity.